PELANGGARAN PENGGUNAAN GAMBAR “LASKAR CINTA” PADA DESAIN PRODUK KAUS BERDASARKAN UNDANG-UNDANG NOMOR 31 TAHUN 2000: Unauthorized Used Of The “Laskar Cinta” Image On T-Shirt Designgs According To Law Number 31 Of 2000 - Laksamana Cristian; Rakhmita Desmayanti (Faculty of Law, Universitas Trisakti, 2024)
A A design is achieved through extensive time, effort, and thought, resulting in a design that sets a product apart from others. For example, the